Generic policy in Bulgaria: a policy of failure or success?. Issue 5 (2nd September 2016) - Stoimenova, Assena; Penkov, Stefan; Savova, Alexandra; Manova, Manoela; Petrova, Guenka
ABSTRACT: Generic medicines play a key role in managing the financial resources for pharmaceuticals in every country. This study analysed the generic policy legislative framework in Bulgaria with the aim to identify whether the policy implementation can be considered successful in the light of an international review of such policies introduced in other countries, or on the contrary, it has failed to deliver the main benefits. Legislative analysis, desktop study and macroeconomic overview of the Bulgarian pharmaceutical market were included. The study showed that only 3 out of 11 important policy elements are implemented in the country. Bulgaria has one of the highest shares of generics, an average of 81.39% (volume), for the studied period (2006–2014). However, further research is needed to evaluate the success of the existing generic policy in Bulgaria, as the market share of generic drugs is not the only measure of the policy efficiency.